In Memoriam: Georgii Ivanovich Zheltov (Ukrainian Journal of Ophthalmology, 2025)
Georgii Ivanovich Zheltov, a distinguished scientist in the field of laser physics and laser ophthalmology, a senior researcher at the Physics Institute of National Academy of Science of Belarus, Dr Sc (Physics and Mathematics), and the Winner of the State Prize of the Republic of Belarus, passed away on November 7, 2020, at the age of 81.